2007
DOI: 10.1097/hpc.0b013e31812da7dc
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Stress Echocardiography in Identifying Significant Coronary Artery Disease in Patients With Left Bundle-Branch Block

Abstract: Stress echocardiography has a poor positive predictive value to identify significant angiographic CAD in higher-risk patients with LBBB; however, the negative predictive value for hard ischemic events is similar to patients without LBBB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Some more recent studies have improved this slightly, perhaps suggesting that more familiarity with the techniques has improved diagnostic accuracy, however, the fact that echocardiography mainly relies on wall motion analysis means that its accuracy, especially in diagnosis of LAD disease is reduced. In a retrospective review of 60 patients who underwent stress echocardiography, Lewis et al found that the technique had a poor specificity (64%) despite a sensitivity of 100% [35]. Positive predictive value was poor at around 40% for patients with or without prior MI.…”
Section: Stress Echocardiographymentioning
confidence: 99%
“…Some more recent studies have improved this slightly, perhaps suggesting that more familiarity with the techniques has improved diagnostic accuracy, however, the fact that echocardiography mainly relies on wall motion analysis means that its accuracy, especially in diagnosis of LAD disease is reduced. In a retrospective review of 60 patients who underwent stress echocardiography, Lewis et al found that the technique had a poor specificity (64%) despite a sensitivity of 100% [35]. Positive predictive value was poor at around 40% for patients with or without prior MI.…”
Section: Stress Echocardiographymentioning
confidence: 99%